2021
DOI: 10.3389/fgene.2020.573344
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphism Variations Associated With Specific Genes Putatively Identified Enhanced Genetic Predisposition for 305-Day Milk Yield in the Girolando Crossbreed

Abstract: Milk production phenotypes are the main focus of genetic selection in dairy herds, and although there are many genes identified as related to the biology of these traits in pure breeds, little is known about crossbreed animals. This study aimed to identify potential genes associated with the 305-day milk yield in 337 crossbreed Gir × Holstein (Girolando) animals. Milk production records were genotyped for 45,613 single-nucleotide polymorphisms (SNPs). This dataset was used for a genome-wide association study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This SNP is located near to KHDRBS3 gene, which is a member of the signal transduction and the activator of RNA (STAR) family proteins. It has been reported that this gene is associated with the 305-day milk yield trait in two cattle breeds: Girolando crossbreed cattle [ 40 ] and primiparous Holstein cows [ 41 ]. Gene network interactions analysis, derived from GWAS-based results, revealed this gene is related to meat quality and growth traits of Brazilian Nelore beef cattle [ 42 ], as well as carcass weight trait in Hanwoo cattle [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This SNP is located near to KHDRBS3 gene, which is a member of the signal transduction and the activator of RNA (STAR) family proteins. It has been reported that this gene is associated with the 305-day milk yield trait in two cattle breeds: Girolando crossbreed cattle [ 40 ] and primiparous Holstein cows [ 41 ]. Gene network interactions analysis, derived from GWAS-based results, revealed this gene is related to meat quality and growth traits of Brazilian Nelore beef cattle [ 42 ], as well as carcass weight trait in Hanwoo cattle [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the NSB trait, a number of candidate genes located within 20 kb of the genome-wide significant and suggestive significant SNPs were identified in both lines. Among them, the NUB1 gene has been reported to be associated with milk production traits in cows and sheep [ 55 , 56 ]. The TGFBR3 gene was also reported to be associated with oocyte maturation in pigs [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since GWASs are ideal for discovering genes that encode complex traits and their mechanisms [ 5 ], they have been widely conducted in recent years to identify relationships between genomic variants and economically significant traits in dairy cattle populations. As a result, a large number of candidate genes and quantitative genomic areas were detected to be associated with economically important traits, including milk-related traits, fertility, growth, and meat and carcass quality [ 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. GWASs conducted in various cattle breeds utilized different SNP chip platforms and were focused on the identification of potential candidate genes and genomic regions responsible for milk production traits including milk yield (MY), fat yield (FY), and protein yield (PY).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported candidate genes (DGAT1, GHR, MAPK15) and SNPs associated with milk production traits are located on chromosome 14 [ 4 ]. Other genes of interest harbored on chromosomes 14 and 20 are GNA14, PTBP2, and U6 which were closely associated with a higher MY [ 6 , 12 , 18 ], respectively. ITPR2 [ 19 ], ABCC9 [ 20 , 21 ], CPSF1 [ 21 ], PDE4 [ 13 ], and METTL15 [ 19 ] genes were reported to influence the expression of FY, while the genes associated with PY were PDHA2 [ 19 ], CTBP2 [ 19 ], MAPK9 [ 22 ], HPS3 [ 23 ], ARFGEF [ 24 ], SLCO1A2 [ 21 ], and MFSD1 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%